Management of Internal Cultural Arts Sanggar Penghulu: Ompek Ganji Limo GonokTradition Festival in Kibul Village - Muyusari, Febra; Asril, Asril; Sastra, Andar Indra (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The purpose of this study is to ascertain how the Ompek Ganji Limo Gonok Oral Tradition festival (OGLG) in West Tabir District is processed by the Sanggar Seni Batin Penghulu. This study employed a qualitative approach, including observation, interviews, and recording; the presenting method was descriptive qualitative. Sanggar Seni Batin Penghulu combines traditional management and modern management. The results of OGLG oral tradition management consist of planning, organization, implementation, and supervision. The planning carried out by the Sanggar Seni Batin Penghulu included creating concepts, coordinating meetings, and dividing work tasks, administrative preparations, and making technical instructions. The organization carried out is the division of work tasks and preparing strategies and tactics to create a festival. The implementation carried out is applying everything that has been designed. This activity consists of an oral tradition competition, an oral tradition workshop, a culinary competition, and an oral tradition performance. The departments responsible for supervision are the Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi, and the Dinas Pendidikan dan Kebudayaan Kabupaten Merangin. The ministry receives direct information on the finances and operations of Sanggar Seni Batin Penghulu Inner Culture.